Primary electron spot-size determination from slit-based measurements for linac photon beams. Issue 7 (July 2016) - O'Brien, Daniel J.; Kinsella, Paul; McCavana, Patrick
Abstract : Monte Carlo models of radiotherapy linacs require the accurate calibration of source parameters including the spot-size of the primary electron beam incident on the target. This parameter is especially important for small field calculations. The calibration of this parameter usually relies on performing small field measurements, which have high uncertainties, and numerous Monte Carlo dose calculations over a range of spot-sizes which is a time consuming process. Here we show that measurements of the collimated photon energy-fluence distribution of a linac beam using a simple movable slit-collimator/detector system can be used as a surrogate to determine the spot-size of the primary electron beam based on a Monte Carlo derived calibration curve. The results of this method were found to be accurate to within (0.1–0.3) mm when compared to an independent method. The calibration curve was derived for an Elekta Precise 6 MV beam but was also found to be robust across a range of beam energies and linac models.